Application of nursing presence to family‐centered care: Supporting nursing practice in pediatric oncology. Issue 1 (4th December 2022) - Mcharo, Solomon K.; Spurr, Shelley; Bally, Jill; Peacock, Shelley; Holtslander, Lorraine; Walker, Keith
Abstract: Purpose: In pediatric care settings, family‐centered care (FCC) is an integral way to ensure family involvement in their child's care and has been known to improve health outcomes and families' psychosocial well‐being. Similarly, nursing presence is deemed beneficial in the formation of authentic nurse–patient relationships and is known to facilitate healing and improve satisfaction for the patient and their family. The objective of this article is to explore how nursing presence supports FCC by closely examining the four concepts of FCC as described by Institute for Patient‐ and Family‐Centered Care: dignity and respect, information sharing, participation, and collaboration. A case study is also presented to demonstrate how nursing presence can be applied in FCC, when caring for a pediatric oncology patient. Conclusion: Nursing presence is essential in FCC since it plays a key role in the formation of relationships, a fundamental element in the four concepts. Attributes of nursing presence can be interwoven in the FCC framework and have positive clinical, social, and emotional outcomes for the patient and family. Although literature has explored associations between FCC and nursing presence, there is need for more scientific research to justify this argument to support the improvement of quality of family nursing care and strengthen the FCC model. Practice Implications: The four concepts of FCC lay a foundation for a model of care that can be enhanced by nursing presence, potentially providing a remedy for depersonalization of healthcare by improving nurse patient relationships in pediatric care settings. Nursing presence becomes less ambiguous when enacted in a FCC framework, revealing attributes that may be cultivated in family nursing to improve therapeutic relationships among nurses and family caregivers.